PENDUGAAN BOBOT BADAN DOMBA GARUT MENGGUNAKAN RUMUS DENMARK MODIFIKASI - Muhammad Maulino Athallah; Pambudi Yuwono; Imbang Haryoko (ANGON: Journal of Animal Science and Technology, 2022)
Backgroound. The research which was carried out at Mitra Tani Farm (MT Farm) aims to determine body weight of Garut sheep using a weighing scale, find out and study the differences in body weight estimation of Garut sheep based on the Danish formula with body weight Garut sheep using weighing scale, and to evaluate modifications to the Danish formula used to estimate the weight of Garut sheep. Materials and Methods. The material used is 18 adult male Garut sheep with an age range of 1-2 years, digital scales with accuracy and measuring tape. The analysis and test used when the research was carried out was using descriptive analysis, t test, correlation test and regression test. Results. Approach by trial and error to get results that have been compared with body weight with a weighing scale to have a difference of 1.41%. Modification of the Danish formula is carried out by changing the numerator from 18 to -10 to obtain a new formula for estimating body weight =(LD(cm) - 10)2/100 and the difference between the modified body weight of the formula and the resulting weight of the weighing scale is 0.07 %. Conculsion. The average of body weight modified by the Danish formula using the numerator -10 is closest to the average body weight using a weighing scale with an R value of 0.923.